Objective Measurement of Medial Joint Space Widening with Percutaneous “Pie Crust” Release of Medial Collateral Ligament during Knee Arthroscopy - Polat, Barış; Aydın, Deniz; Polat, Ayşe Esin; Gürpınar, Tahsin; Sarı, Enes; Özmanevra, Ramadan; Yalçınozan, Mehmet; Erler, Kaan (The Journal of Knee Surgery, 2020)
Knee arthroscopy may be called the most commonly and increasingly performed orthopaedic procedure. Posterior medial compartment visualization may be quite challenging. The aim of the present study is to detect objective measurement of medial joint space widening with percutaneous “pie crust” release of medial collateral ligament (MCL) during knee arthroscopy. We used this technique for all knees that require any intervention in the posteromedial compartment and for tight knees in which adequate visualization of the posteromedial compartment cannot be obtained. Eighteen patients (18 knees) were included in this study. Patients were evaluated clinically with the Lysholm and Tegner scores at the final office visit. Joint balance, valgus instability, pain or tenderness on MCL region, and numbness over the medial side of the joint were also noted. Measurements of medial joint space (mm) were obtained at three different times with perioperative C-arm images: normal, controlled valgus force, and after pie crusting. The median follow-up time was 9 (6–12) months. Final follow-up Lysholm (p < 0.05) and Tegner scores (p < 0.05) increased significantly compared with preoperative scores. At the final follow-up, there was no pain or tenderness over MCL and there were no signs of saphenous nerve or vein injury. Medial joint space values in after pie crusting increased significantly (p < 0.05) compared with neutral position measurements and controlled valgus force application (p < 0.05). Controlled release of the MCL in knees provided ∼2.45 times wider visualization place. Furthermore, pie crusting of MCL is a safe and effective technique that provides enough space for visualization and instrumentation in knees. This is a Level IV study.
Keywords: pie crust; knee arthroscopy; medial collateral ligament release